If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 55 = 6 + -2h Solving 55 = 6 + -2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '2h' to each side of the equation. 55 + 2h = 6 + -2h + 2h Combine like terms: -2h + 2h = 0 55 + 2h = 6 + 0 55 + 2h = 6 Add '-55' to each side of the equation. 55 + -55 + 2h = 6 + -55 Combine like terms: 55 + -55 = 0 0 + 2h = 6 + -55 2h = 6 + -55 Combine like terms: 6 + -55 = -49 2h = -49 Divide each side by '2'. h = -24.5 Simplifying h = -24.5
| 8+k/2.5=14 | | 1.5x=2.52 | | 1369000000=10n | | 6+2k=-12 | | 1369000000=10 | | -4(x+1)+2=8 | | 18c^4-9c^2+7c=0 | | sqr(4x+1)+1=40 | | 10-2(x-1)=8 | | 4x^3+12x^2+16x=0 | | -(-2v-6)=-3-5(v+8) | | -2(8u-7)+4u=2(u+6) | | 2/3(x-6)-1/3(x-3) | | -2(8u-7)+4v=2(v+6) | | 2w^3+6w^2-4w=0 | | 90d=2 | | -(3-3n)=4(7+2n)+4 | | 81+2d= | | -2n+8(n-7)=-86 | | 6a^3-12a^2+14a=0 | | -3(2-1)=12 | | -2n+8(n-7)=-3-5(v+8) | | 18=69-24 | | L=b+c-dsolvec | | 10w+10+3w=6(9+w)-14 | | 8+7n-6-4n=n-8 | | (2x^2-13x+6)/(6x^2-x-1) | | 8x-9=41 | | 3m(m+4)=18 | | 6x-3=7x-10 | | 1/3(3x-2)=6-x | | 2n+3+8=1 |